Phonngān wičhai r̄ưang wichāchīpniyom kh̨̄ong khārātchakān Sathāban Phatthanā Khārātchakān Phonlar̄ưan, Samnakngān K̨̄o. Ph̨̄o. - Phačhongčhit Rattanōthayānon (Phāk Wichā Ratthaprasāsanasāt, Čhulālongk̨̄onmahāwitthayālai, 1993)
Study on professionalism in officials of Civil Service Training Institute.